The Role of East Java as A Trade Hub for Eastern Indonesia - Muhammad Dzul Fadlli (East Java Economic Journal, 2022)
The role of East Java as a trade hub for eastern Indonesia is still in doubt. This study aims to analyze the role of East Java as a trade hub for eastern Indonesia (KTI). This research was conducted descriptively using interregional input-output (IRIO) data with 52 industries in 2016 from BPS. The results of this study show that the proportion of East Java's exports to eastern Indonesia is still small. Although small in proportion, exports by East Java to eastern Indonesia are very profitable for East Java. The value of East Java's exports is greater than the value of its imports. The majority of East Java's exports are used to meet final demand needs. Meanwhile, imports by East Java from eastern Indonesia are dominated by intermediate demand in East Java. Bali is East Java's largest export destination in Eastern Indonesia, followed by Papuan, NTB and NTT. Industries with dominant export values ??to eastern Indonesia include the Food and Beverage Industry and the Tobacco Processing Industry. Meanwhile, the dominant imports came from a season and annual plantation industry and the metal ore mining industry.